Isokinetic strength profiles of thigh muscles of modern dancers in relation to their experience level - KURTEL, HIZIR (My University, 2013)
The aim of this study was to determine maximal voluntary peak torque (PT), PT% body weight (PT%BW), total work (TW), and hamstring/quadriceps ratio (HQR) for bilateral and unilateral thigh muscle strength during isokinetic muscle contractions in modern dancers in relation to their experience level. METHODS: Twenty-two female dancers were divided into two groups: intermediate dancers (ID, n=11) and advanced dancers (AD, n=11). Strength tests were performed using the Biodex System-III Pro Multijoint System isokinetic dynamometer to determine three joint angular velocities (60, 180, 300°/s). RESULTS: During extension, ADs exhibited higher ratios in the HQR (p=0.016) on right leg at 300°/s, IDs generated greater TW (p=0.042), and within groups, there was a significant left-to-right difference in the HQR at 300°/s for ADs (p=0.042). During flexion, within groups, the ADs exhibited significant differences between legs for both PT (p=0.026) and PT%BW (p=0.022) at 300°/s. CONCLUSION: For both groups, the average HQR in all angular velocities was not within the recommended range, which is required to prevent injuries; at the same time, unilateral muscular imbalances existed. Lower extremities of ADs exhibited asymmetric strength patterns at a certain level. Further research should be done to confirm the findings of this pilot study. © 2013 Science & Medicine.
Keywords: Sosyal ve Beşeri Bilimler; Felsefe; Bilim Tarihi; Sosyoloji; Social Sciences and Humanities; Philosophy; History of Science; Sociology; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; BİLİM TARİHİ VE FELSEFESİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; HISTORY & PHILOSOPHY OF SCIENCE; Bilim Tarihi ve Felsefesi; Sosyal Bilimler ve Beşeri Bilimler; History and Philosophy of Science; Social Sciences & Humanities